2015
DOI: 10.1590/0103-8478cr20141508
|View full text |Cite
|
Sign up to set email alerts
|

A grazing height target to minimize tiller stem elongation rate in annual ryegrass swards

Abstract: Italian ryegrass (Lolium multiflorumLam

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…Adicionalmente, é possível que essa cultivar tenha se beneficiado da disponibilidade de nutrientes, não priorizando somente a produção de folhas, mas também de pseudocolmos. Segundo Santos et al (2016), a taxa de alongamento de colmos em perfilhos de azevém anual aumenta rapidamente quando os pastos atingem 18 cm de altura, mesmo onde há uma relativa baixa competição por luz (ou seja, em pastos semeados em linha), uma vez que o alongamento de colmos parece ser um processo inevitável.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Adicionalmente, é possível que essa cultivar tenha se beneficiado da disponibilidade de nutrientes, não priorizando somente a produção de folhas, mas também de pseudocolmos. Segundo Santos et al (2016), a taxa de alongamento de colmos em perfilhos de azevém anual aumenta rapidamente quando os pastos atingem 18 cm de altura, mesmo onde há uma relativa baixa competição por luz (ou seja, em pastos semeados em linha), uma vez que o alongamento de colmos parece ser um processo inevitável.…”
Section: Resultsunclassified
“…Os pastos foram rebaixados por meio de "mob-grazing", com equinos da raça Crioulo e alturas em pré-e pós-pastejo de 25 e 10 cm, respectivamente. As metas de manejo foram baseadas em resultados prévios obtidos por Santos et al (2016), onde pastos de azevém anual manejados com alturas em pré-pastejo entre 15-25 cm e rebaixados para 8 cm, não apresentavam diferenças nas taxas de acúmulo de folhas.…”
Section: Methodsunclassified
“…This assumption is supported by work conducted by Amaral et al (2012), who observed a maximum STIR at a 60% defoliation level for annual ryegrass swards during the first grazing cycles. Additionally, Santos et al (2016) examined annual ryegrass pastures during vegetative stages and under intermittent stocking methods, and the results indicated no reductions in herbage and leaf production when the level of defoliation was higher than 50% of the pre-grazing height, when associated with the same post-grazing targets. Moreover, defoliation exceeding 40% of the pre-grazing sward surface height during the first grazing cycles might stimulate tillering and delay stem + pseudostem elongation, which would maintain a greater percentage of leaves in the sward (both pre-and post-grazing) throughout the growing season (Miguel et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The pastures were managed under an intermittent stocking method with pre-grazing heights of 23, 17 and 20 cm for black oat, annual ryegrass and intercropped pastures, respectively. The pre-grazing height used for annual ryegrass was determined based on previous experiments, which indicated an elevated stem elongation rate starting from 18 cm (Santos et al , 2016). For black oat, because of a lack of information, height was determined by plant structure, which is slightly taller compared to annual ryegrass, generating an intermediate height between both species for the intercropped pastures.…”
Section: Methodsmentioning
confidence: 99%